Silencing Trauma Survivor in Timor-Leste: Women’s Domestication in Beatriz’s War - Putri Rania Abida; Uci Elly Kholidah; Zietha Arlamanda Asri (Sabda: Jurnal Kajian Kebudayaan, 2026)
Indonesian occupation in Timor-Leste caused a destructive damage upon Timorese, especially women. Beatriz’s War (2013) presents a representation of multiple violence experienced by Beatriz, the main character of the movie throughout her life. This study aims to analyze the multiple violence experienced by Beatriz and how domestication of women contributes to the silencing of her traumatic testimony based on Felman and Laub (1992) framework on witnessing and testimony. The data were collected through visual and narrative analysis of selected excerpts. The result of this study shows that Beatriz undergoes fourfold violence which is physical, psychological, gendered, and structural violence. The result of this study shows that domestication within patriarchal society, such as limiting women within domestic roles, contributes to the misrecognition of her trauma. This study highlights how patriarchal norms and women confinement to domestic sphere serve to disregard the voices of survivors in post-war community